Managing the motivation provision of universities in the context of the educational process digitalisation - T. V. Kuzminova; O. L. Belova (Вестник университета, 2022)
The paper proposes a method for increasing the motivation of university teachers to work with digital technologies on the example of teaching foreign languages. The fear of complete displacement of the teacher by digital technologies leads to many ethical and psychological problems, resulting in a reluctance to use training programmes in the educational process. To increase the motivation of teachers to work in the digital environment, it is proposed to involve them in the use of digital educational technologies to adapt the work plans of disciplines to the preparation level of students entering universities. The specialists team composition required for the implementation of this method in practice has been formed. Additional factors for increasing the teachers motivation to work in a digital environment when working in a team have been shown. The proposed approach can be used in the implementation in digital educational systems of educational institutions.